2022
DOI: 10.1007/s00360-022-01451-8
|View full text |Cite
|
Sign up to set email alerts
|

State dependence of arousal from torpor in brown long-eared bats (Plecotus auritus)

Abstract: To cope with periods of low food availability and unsuitable environmental conditions (e.g., short photoperiod or challenging weather), many heterothermic mammals can readily go into torpor to save energy. However, torpor also entails several potential costs, and quantitative energetics can, therefore, be influenced by the individual state, such as available energy reserves. We studied the thermal energetics of brown long-eared bats (Plecotus auritus) in the northern part of its distributional range, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…A few empirical studies have demonstrated state dependency regarding torpor expression in heterotherms, where animals with more energy reserves spent less time torpid, for example woodchucks ( Marmota monax : Zervanos et al, 2014), dormice ( Glis glis : Bieber et al, 2014), and bats ( Myotis myotis : Wojciechowski et al, 2007; Myotis lucifugus : Matheson et al, 2010; Plecotus auritus : Sørås et al, 2022). As expected, our model predictions of daytime torpor use are consistent with these findings, showing that individuals with lower energy reserves benefit to a greater extent from torpor energy savings, whilst individuals with greater energy reserves benefit from instead spending more time awake and resting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few empirical studies have demonstrated state dependency regarding torpor expression in heterotherms, where animals with more energy reserves spent less time torpid, for example woodchucks ( Marmota monax : Zervanos et al, 2014), dormice ( Glis glis : Bieber et al, 2014), and bats ( Myotis myotis : Wojciechowski et al, 2007; Myotis lucifugus : Matheson et al, 2010; Plecotus auritus : Sørås et al, 2022). As expected, our model predictions of daytime torpor use are consistent with these findings, showing that individuals with lower energy reserves benefit to a greater extent from torpor energy savings, whilst individuals with greater energy reserves benefit from instead spending more time awake and resting.…”
Section: Discussionmentioning
confidence: 99%
“…The different daily temperature cycles in the roost (Figure S1.1a, dashed lines) were estimated using our own collected field‐data (see Supplementary Materials 1), which further impacted metabolic costs, obtained from studies quantifying these across temperature ranges (Fjelldal et al, 2022; Geiser & Brigham, 2000; Turbill, 2008; Figure S1.1b), while outside air temperatures (Figure S1.1a, solid lines) affected prey availabilities (Speakman et al (2000); Figure S1.1c). For simplicity, hourly flight cost (calculated from the study by Kurta et al, 1989, see Supplementary Materials 1) and energy gain (calculated from the study by Sørås et al, 2022, see Supplementary Materials 1) were included as static values (Table S1.1b), and the estimated predation threat and competition cost in the model did not differentiate between day‐types (Figure S1.1d). However, we added a slight increase in predation threat with level of energy reserves in line with published estimates of mass‐dependent flight costs (Aldridge, 1987; Anthony & Kunz, 1977; Witter & Cuthill, 1993), which broadly tally with observations of heavy individual bats being more light avoiding (Speakman, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Here we show that a pivotal turning point in torpor use occurs in late summer, leading to increased reliance on daily torpor as bats likely compensate for declining insect availability during the fat-building phase. The underlying factors contributing to this turning point remain unknown and may be associated with temperature variations, rapid autumnal temperature declines at these latitudes favoring torpor in cold roosts (Speakman & Rowland, 1999), body mass considerations (Sørås et al, 2022), night length (Turner & Geiser, 2016), or a combination thereof. Moreover, after bats fully shift to employing daily torpor in early September, they also begin to increase torpor during the night.…”
Section: Roost Type Effects On Torpor Dynamicsmentioning
confidence: 99%
“…Torpor patterns can vary among bat species, influenced by factors such as their ecological niche, geographic location, and the availability of resources (Stawski & Geiser, 2010; Boyles et al, 2017). Bats with a greater body mass exit torpor at lower ambient temperatures, whereas those with a lower body mass delay arousal until temperatures are higher (Sørås et al, 2022). This implies that bats may, based on their individual state, adjust their level of thermoregulation at different temperatures, potentially to alleviate the associated costs of torpor (Sørås et al, 2022) or to obtain physiological or ecological benefits from being active (Fjelldal et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%